Evaluation of surface water quality using multivariate statistical techniques: a case study of Fei-Tsui Reservoir basin, Taiwan - Chow M.F.; Shiah F.K.; Lai C.C.; Kuo H.Y.; Wang K.W.; Lin C.H.; Chen T.Y.; Kobayashi Y.; Ko C.Y. (Springer Verlag, 2023)
Biochemical oxygen demand; Cluster analysis; Discriminant analysis; Dissolved oxygen; Hierarchical systems; Multivariant analysis; Organic pollutants; Pollution; Potable water; Principal component analysis; Reservoir management; Reservoirs (water); River pollution; Sampling; Statistical methods; Surface waters; Turbidity; Water; Water pollution; Water quality; Hierarchical cluster analysis; Multivariate statistical techniques; Non-point sources pollutions; Restoration and protection; Spatiotemporal patterns; Sustainable management; Total dissolved solids; Water quality variations; Quality control; anthropogenic source; biochemical oxygen demand; cluster analysis; discriminant analysis; dissolved oxygen; drinking water; nonpoint source pollution; organic pollutant; principal component analysis; reservoir; river basin; surface water; water quality; water temperature; Taiwan